REVOLVING LOAN EVALUATION OF NATIONAL PROGRAM FOR COMMUNITY EMPOWERMENT - SELF CONTAINED URBAN (PNPM-MP) ECONOMIC SECTOR IN SOROSUTAN, UMBULHARJO SUBDISTRICT YOGYAKARTA - Azhar Aditya Rahman; Dyah Lituhayu (Journal of Public Policy and Management Review, 2012)
National Program for Community Empowerment-self containedUrban (PNPM-MP) is an empowerment program initiated by the central government since 2006. One of the development undertaken is in the economic field with the revolving loan program. This revolving loan is a loan that is destined for the poor village. The goal is to provide access to finance for the poor as additional capital for those who have a business and would pioneering effort and will teach the poor in managing finances. Sorosutan Village become one of the revolving loan program that implementing it. Arising phenomena from the implementation of this program in Sorosutan Village was the question of the level of bad debts tend to have increased in recent years.This study was exploratory in interview technique. Sources of data obtained from the primary data through interview with key informant or person. While secondary data derived from data of documents, archives and other sources related to research. Data were analyzed with a triangulation method for checking the source or as a comparison of the data.From evaluation was known that the implementation of a revolving loan program was viewed from the aspect of effectiveness, efficiency, responsiveness, timeliness, adequacy and alignment was quite good. Although the learning in terms of financial management for the poor still need strengthening in terms of assistance. The program was able to provide easy access to financial services and was able to address poverty at village level by improving the economy of the poor village. Bad debts were likely to increase in recent years was because mentoring and supervision conducted field is still weak, so the use of the fund provided was not monitored regularly. This led to misappropriation of fund at community level is high. The existence of an earthquake in 2006 also contributed to the increasing number of Non Government Organizations (NGOs) were exposed to bad loans.